Pengaruh Digital Marketing dan Digital Payment Terhadap Keputusan Pembelian pada Marketplace Shopee oleh Mahasiswa Fakultas Ekonomi Undiksha - Yanti, Putu Nonik Panya; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to determine the effect of digital marketing and digital payment on purchasing decisions at the Shopee Marketplace by students of the Faculty of Economics, Undiksha. This research is quantitative causal research. The population used in this study was a student of the Faculty of Economics, semester 1.3, 5, and 7, a total of 2,747 students. The sampling technique used in this study was Proportional Random Sampling with a total sample of 190 respondents. The method of data collection in this study is the dissemination of questionnaires. The data analysis used in this study is a double linear regression analysis. The results of this study are: (1) there is a positive and significant influence of digital marketing variables on purchasing decisions, (2) digital payment variables have a significant and positive influence on buying decisions, and (3) digital marketing and digital payments simultaneously have a positive, significant impact on purchase decisions.